Soft apoptotic-cell-inspired nanoparticles persistently bind to macrophage membranes and promote anti-inflammatory and pro-healing effects. (1st September 2021) - Zhang, Guanglin; Xue, Haoyu; Sun, Dazheng; Yang, Shenyu; Tu, Mei; Zeng, Rong
Abstract: Macrophages play a key role in inflammation, infection, cancer, and repairing damaged tissues. Thus, modulating macrophages with engineered nanomaterials is an important therapeutic strategy for healing chronic inflammatory injuries. However, designing and manufacturing therapeutic nanomaterials remains challenging. Therefore, in this study, apoptotic-cell-inspired deformable phosphatidylserine (PS)- containing nanoliposomes (D-PSLs) with a Young's modulus (E) of approximately 0.5 kPa were constructed via a facile and scalable method. Compared with similar-sized conventional PSLs with an E of approximately 80 kPa, the d -PSLs had a lower uptake efficacy, a much longer binding time to the cell surface, and induced enhanced anti-inflammatory and pro-healing effects via the synergistic effects of their mechanical stimulus and PS-receptor mediation after recognition by macrophages. In particular, chronic wound healing in diabetic rats showed that d -PSLs can efficiently promote M2-like macrophage polarization, increase the expression of the vascular endothelial marker CD31 and accelerate wound closure. Our findings suggest that soft d -PSLs represent a promising biomimetic nano-therapeutic approach for macrophage immunotherapy for chronic inflammatory injury, and that the mechanical stimulus of nanomaterials significantly affects the receptor-mediated biological responses, which will inspire the design of engineered nanomaterials for biomedical applications. Statement of significance: Macrophages play a significant role in restoring tissue homeostasis by modulating inflammation and wound healing. Specifically, an M1/M2 macrophage imbalance contributes to various inflammatory disorders. However, modulating macrophages with engineered nanomaterials remains a challenge. In this study, apoptotic-cell-inspired deformable phosphatidylserine (PS)- containing nanoliposomes (D-PSLs) were constructed to explore their interactions with macrophages, and evaluate their anti-inflammatory and pro-healing effects on chronic wounds in diabetic rats. We found that soft d -PSLs can persistently bind to macrophage membranes and enhance the anti-inflammatory and pro-healing responses of macrophages, which not only sheds new light on the design of therapeutic biomaterials based on regulating macrophages but also provide a promising biomimetic nano-therapeutic approach for chronic inflammatory injury. Graphical abstract: Image, graphical abstract